Performance of Elite Sugarcane Genotypes in North Coastal Zone of Andhra Pradesh - Gouri, V.; Rajkumar, N.; Bharathalakshmi, M.; Chitkaladevi, T.; Appalaswamy, A. (International Journal of Bio-resource and Stress Management, 2020)
A study was conducted at RARS, Anakapalle to evaluate the performance of promising early sugarcane genotypes during 2016-17 under AICRP on Sugarcane. Among different elite clones CoA 12322 (2006 A 102) which is developed from 88 R 13 GC performed better and this genotype was tested against the popular checks Co 6907, Co C 01061 and Co A 92081 along with other zonal varieties Co A 12321, CoA12323, Co Or 12346 and Co V 12356. Co A 12322 (2006 A 102) recorded highest cane yield of 89.8 t ha-1 as compared to standards, Co 6907 ( 86.1 t ha-1), Co C 01061 (84.1 t ha-1) and Co A 92081 (77.8 t ha-1) and also highest CCS yield of 9.7 t ha-1 as compared to standards, Co 6907(9.3 t ha-1), CoC 01061 (8.8 t ha-1) and CoA 92081(9.0 t ha-1). Per cent juice sucrose and commercial cane sugar per cent in Co A 12322 (18.0 and 11.1) was on par with Co 6907(17.2 and 10.85) CoC 01061 (17.7 and 10.44) and Co A 92081 (16.7 and 11.63) when tested in Anakapalle of East coast zone. It is resistant to all three pathotypes of red rot both under natural, cotton swab method and artificially inoculated conditions (Plug method). It was resistant to wilt, susceptible to smut and moderately resistant to Yellow Leaf Disease. The clone can be distinguished by chrome yellow with purple tinge cane, green foliage without any waxy coating on leaf sheath and easily trashable.